EVALUASI KEINDAHAN LANSKAP PANTAI BALEKAMBANG DI DESA SRIGONCO KABUPATEN MALANG - Putra, Anshori Andy; Djoko, Riyanto; Budiyono, Debora (Fakultas Pertanian, 2017)
Coast landscape is one of the region that have resources being diverse and the potential that beautiful .One of several shores visual having a beautiful coast is Balekembang which is located in the Village Srigonco , Districts Bantur , Malang district. Research aims to 1 ) determine and assess the quality of visual landscape tourism area based on the coast of Balekembang prediction beauty. 2 ) determine landscape zone the beauty of the coastal zone Balekembang perceptions of respondents . 3 ) make recommendations model landscape design the arrangement coast tourist Balekambang prediction based on the quality of visual. The research was done in the coastal Balekembang, Village Srigonco, Districts Bantur , Malang district , East Java. The time of this study was conducted for 6 months namely months November-may 2016. The quality of visual prediction carried out through a method of SBE? = (Z?? ? Z?o)X100. From the results of questionnaire done inputing data in the form of scoring tabulation respondents. Using distribution of the value of 1-10 rating. Intervals the values been divided into three class beauty ( high , being , and low ). Analysis undertaken , known that the total amount of SBE is highest in landscape 1 , 37 , 12 , 50 , 36 , 44 , 34 , 51 , 52 , 47 , 8 , 43 , 33 , 41 , 53 , 6 , 35 , and 54 the average value of between 97-64 .The category of visual being is found in a landscape 17 , 56 , 40 , 49 , 5 , 13 , 39 , 55 , 45 , 32 , 46 , 48 , 21 , 9 , 27 , 28 , and 25 63-32 with a value of .The category of visual low landscape is found in 29 , 42 , 19 , 11 , 38 , 31 , 16 , 3 , 26 , 18 , 14 , 10 , 20 , 4 , 22 , 15 7 , 23 , 2 , 30 , and 24 with a value of 31-0 . Lanskap pantai merupakan salah satu kawasan yang memiliki sumber daya yang beragam dan potensi yang indah. Salah satu pantai yang memiliki visual yang indah adalah Pantai Balekambang yang berada di Desa Srigonco, Kecamatan Bantur, Kabupaten Malang. Penelitian ini bertujuan untuk 1) Menentukan dan menilai kualitas visual lanskap kawasan wisata Pantai Balekambang berdasarkan pendugaan keindahan. 2) Menentukan zona keindahan lanskap kawasan Pantai Balekambang berdasarkan persepsi responden. 3) Membuat rekomendasi model desain penataan lanskap wisata pantai Belekambang berdasarkan pendugaan kualitas visual. Penelitian dilakukan di kawasan Pantai Balekambang, Desa Srigonco, Kecamatan Bantur, Kabupaten Malang, Jawa Timur. Waktu penelitian dilakukan selama 6 bulan yaitu bulan November-bulan Mei 2016. Pendugaan kualitas visual dilakukan melalui metode SBE? = (Z?? ? Z?o)X100. Dari hasil kuesioner dilakukan inputing data dalam bentuk tabulasi scoring responden menggunakan sebaran nilai rating 1-10. Interval nilai tersebut dibagi menjadi 3 kelas keindahan (tinggi, sedang, dan rendah). Analisis yang dilakukan, diketahui bahwa nilai SBE tertinggi terdapat pada lanskap 1, 37, 12 , 50, 36, 44, 34, 51, 52, 47, 8, 43, 33, 41, 53, 6, 35, dan 54 dengan nilai rata-rata antara 97-64. Kategori kualitas visual sedang terdapat pada lanskap 17, 56, 40, 49, 5, 13, 39, 55, 45, 32, 46, 48, 21, 9, 27, 28, dan 25 dengan nilai 63-32. Kategori kualitas visual rendah terdapat pada lanskap 29, 42, 19, 11, 38, 31, 16, 3, 26, 18, 14, 10, 20, 4, 22, 15 7, 23, 2, 30, dan 24 dengan nilai 31-0.